1999
DOI: 10.1007/s00585-999-1260-5
|View full text |Cite
|
Sign up to set email alerts
|

Two types of ELF hiss observed at Varanasi, India

Abstract: Abstract. The morphology of ELF hiss events observed at low-latitude ground station Varanasi (L = 1.07, geomagnetic latitude 14°55¢N) are reported, which consist of two types: (1) events which propagated in ducted mode along the geomagnetic ®eld line corresponding to observing station Varanasi and (2) events which propagated in ducted mode along higher L-values (L = 4±6), after reaching the lower edge of ionosphere excite the Earth-ionosphere wave guide and propagate towards equator to be received at Varanasi.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…At low latitude, nights with observable VLF emissions are rather rare, and the activity is closely related to strong magnetic storms (Singh, 1993). But when it appears its occurrence rate is comparable to that of mid latitude (Singh, 1993;Singh et al, 1999). The observations of discrete VLF emissions at low latitude ground stations Varanasi, Jammu and Gulmarg are unusual in the sense that most of the reported observations are from satellites (Cornilleau-Wehrlin et al, 1978;Hattori et al, 1991;Santolik et at., 2004) or from high latitudes.…”
Section: Experimental Observation and Analysismentioning
confidence: 89%
“…At low latitude, nights with observable VLF emissions are rather rare, and the activity is closely related to strong magnetic storms (Singh, 1993). But when it appears its occurrence rate is comparable to that of mid latitude (Singh, 1993;Singh et al, 1999). The observations of discrete VLF emissions at low latitude ground stations Varanasi, Jammu and Gulmarg are unusual in the sense that most of the reported observations are from satellites (Cornilleau-Wehrlin et al, 1978;Hattori et al, 1991;Santolik et at., 2004) or from high latitudes.…”
Section: Experimental Observation and Analysismentioning
confidence: 89%
“…At low latitude, nights with observable VLF emissions are rather rare, and the activity is closely related to strong magnetic storms. However, during nights with chorus emissions the occurrence rate is comparable to that at mid latitude (Singh, 1993;Singh et al, 1999Singh et al, , 2000. Several interesting VLF events were recorded during the period January to July 1986 at the low-latitude ground station Gulmarg (geomag.…”
Section: Chorus Observationsmentioning
confidence: 89%
“…The early observations of low latitude ground-based VLF hiss comes from Japanese workers [50][51][52] and later on from Indian workers [4,53]. VLF hiss at Srinagar, India was recorded in the frequency band 1-3 kHz and 5-7 kHz [53].…”
Section: Experimental Datamentioning
confidence: 99%
“…Global distribution of hiss is characterized by three principal zone of intense activity of which the first zone is located around invariant latitudes above 70 AE (auroral hiss), the second near 50 AE (mid-latitude) and the third below 30 AE latitude (equatorial hiss) [3]. Ground-based observations revealed that the low-latitude hiss are less intense than those observed at middle and high latitudes [4,5]. Jorgensen [6] analyzed amplitude distribution of hiss and showed that it decreased with decreasing latitude (10 dB per 1000 km) and explained it in terms of attenuation of hiss emission propagating through the earth-ionosphere wave guide from auroral zone to middle and low latitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation